Pharmacognostic Studies on Tradescantia Zebrina - Gouri Kumar Dash; Mohamad Nur Aiman Fadrul; Allan Mathews (Journal of Global Pharma Technology, 2018)
Tradescantia zebrina Heynh. ex Bosse (Family- Commelinaceae), is an important medicinal plant with several traditional medicinal uses. In Malaysia, the plant is recommended to be a remedy to improve kidney function. In the present paper, we report some pharmacognostic studies on the leaves since there are no standard parameters available for this plant in the literature. Presence of typical epidermis with multiple hypodermis layers, few chloroplasts scattered in the spongy parenchyma and red color in most parts of the upper and lower epidermis are some of the key features for the identification of the species. Preliminary phytochemical screening of leaves showed presence of sterols, saponins, flavonoids, tannins, carbohydrates, and proteins and amino acids respectively. The above findings together with physicochemical parameters can be useful in establishing pharmacognostic standards for the plant.